'Makes you wanna do treatment': Benefits of a hepatitis C specialist clinic to clients in Christchurch, New Zealand. (1st December 2012) - Brener, Loren; Gray, Rebecca; Cama, Elena J.; Treloar, Carla
Abstract: People with hepatitis C virus (HCV) are a marginalised population that may experience discrimination in everyday contexts, including health‐care, due to the association of HCV with injecting drug use. Stigma and discrimination are known to have a range of negative effects on people with HCV, including diminished quality of life and avoidance of health‐care. The Hepatitis C Community Clinic is an integrated care service established in 2008 in Christchurch, New Zealand to provide alternative access to health‐care that is non‐judgemental and supportive. As an integrated care service, the clinic aims to improve health outcomes and quality of life through a holistic approach to health‐care for people with HCV and people who inject drugs. This qualitative study forms part of a broader mixed‐methods evaluation of the clinic, and aims to assess the role of the clinic in improving health outcomes, knowledge, lifestyle practices and psychosocial functioning of the target population. Interviews were conducted with 24 health professionals and 24 clients of the clinic between April and November 2010. Findings illustrate that the clinic is a novel model of care that is effective in accessing a hard‐to‐reach and marginalised population in part due to the non‐judgemental, caring and supportive environment that engenders trust with clients. Based on participant reports, the clinic assists clients in managing their HCV and other health concerns and in increasing their readiness for HCV treatment. Given the benefits of this community clinic to clients, it is proposed that future research investigate the feasibility and benefits of administering HCV treatment through community‐based integrated care networks.